Covid 19- An Orthodontists’ perspective (Orthodontic Journal of Nepal, 2020)
COVID 19 has created havoc in the entire world in past few months. Starting from Wuhan, China the disease has spread to the entire world in couple of months. The highly contagious and notorious nature of the disease has made WHO declare it as a pandemic and sixth public health emergency of international concern. The nature and course of disease is constantly being upgraded by the researchers all over the world. Amongst all the health professionals, Dental fraternity is at utmost risk due to the mode of spread of infection via respiratory droplets. The fact has lead to increased anxiety amongst the fraternity and orthodontists are not an exception to it. In this article, an effort has been taken to summarise and review the cause and effects of SARS CoV 2, the precautions to be taken by the orthodontists and patients during the pandemic and smooth re opening of the practice post lockdown so as to minimise the anxiety and serve the patients in a safer way.